College Athletes and NCAA Regulations - Larry, Kaleb Artaz (My University, 2020)
The NCAA was formed in 1906, it was previously known as the Intercollegiate Athletic Association (ICAA) of the United States, its goal was to guide students to the best possible institutions for their skillsets. Shortly after the ICAA organization was formed, universities started to give incentives for athletic participation by offering tuition discounts in hopes of persuading students to attend their schools. In 1952, scholarships for athletics became legal. Additionally, the later National Collegiate Athletic Association (NCAA) implemented policies to protect students from “exploitation”, and to determine the manner and amount of money that could be given. As a result, the NCAA created regulations that it claimed were best for student athletes. Critics of these regulations, however, claim that they keep amateur athletes from achieving the financial security necessary to complete their education while funneling all profits to the NCAA. This paper will examine the NCAA regulations and their impact on student athletes. Issues of student athlete poverty and NCAA profits will be examined in order to determine the legitimacy of these regulations. Finally, the paper will examine the recent move by the NCAA to allow student athletes to profit from the use of their images and how this fails to assist athletes that are not deemed “stars”.